The Secret Of Bengkulu Coffee Shops: Flavor Innovation, Business Strategy, And Operational Resilience - Afrida Rianjani; Marvi Hasvick; Karona Cahya Susena; Muhammad Rahman Febliansa (Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
As one of the largest Robusta coffee-producing regions in Indonesia, Bengkulu has experienced a rapid surge in the growth of coffee shops. This research aims to uncover the secrets to the success and sustainability of local coffee shop Micro, Small, and Medium Enterprises (MSMEs) through an analysis of the synergy between Flavor Innovation, Business Strategy, and Business Resilience. Using a qualitative approach with an exploratory case study design on Kraving Cafe and Ikola Koffie, data was collected through interviews and observation. The results indicate that success is driven by Authentic Local Flavor Innovation, Locality-Based Differentiation Strategy and Multiplatform Digital Adoption, as well as Business Resilience through Supply Chain Resilience and Income Diversification.